Are adults with asthma less physically active? A systematic review and meta-analysis. (2nd November 2021) - Xu, Min; Lodge, Caroline J.; Lowe, Adrian J.; Dharmage, Shyamali C.; Cassim, Raisa; Tan, Daniel; Russell, Melissa A.
Abstract: Objective: To systematically review the evidence on whether having current, ever asthma and asthma control is associated with levels of total, moderate and vigorous physical activity. Methods: We searched EMBASE, MEDLINE, and CINAHL databases, limiting searches to English language papers from inception until Oct 2019. We synthesized the evidence comparing levels of total, moderate and vigorous physical activity between adults with and without current asthma or ever asthma by random effects meta-analyses. Results: A total of 25 studies were included, with 18 of these included in meta-analyses. A meta-analysis of 4 case-control studies found that adults with current asthma were less active, with 942.12 steps fewer per day, than adults without current asthma (SMD = −0.39, 95%CI: −0.54, −0.24, I 2 = 0). Meta-analysis of four-high quality cross-sectional studies found that those with current or ever asthma were more likely to be inactive than those without asthma (binary OR current asthma = 0.85, 95%CI: 0.82, 0.89, I 2 = 45.6%, and binary OR ever asthma = 0.83, 0.75, 0.91, I 2 = 0, respectively). Meta-analysis, inclusive of all 10 cross-sectional studies with binary ORs, supported this finding. There was also some evidence that adults with current asthma and ever asthma (6 studies with categorical ORs) were less likely to exercise moderately and vigorously, but these meta-analyses were limited by high heterogeneity. No synthesis of the studies considering asthma control was possible. Conclusion: Adults with current or ever asthma had lower levels of total, moderate and vigorous physical activity than those without asthma and may be missing out on the health benefits of being physically active. The association between asthma control and physical activity warrants further investigation.